Static action, silent sound: Translating visual techniques from manga to film in Katsuhiro Ō-tomo's AKIRA. Issue 1 (1st April 2014) - Gangnes, Madeline B.
In the manga AKIRA (1982–1990), Katsuhiro O-tomo depicts action sequences, violence and the presentation of space through a visual approach that expertly creates a dynamic sense of movement and presence within the moment. This effect is achieved through the manipulation of the form and structure of the comics page, particularly through the use of a cantilevering technique to unbalance the page structure and make the action sequences feel visceral and tense. To that end, O-tomo also uses embodied perspectives, eye-line matches and appeals to the senses, especially sound. O-tomo strives to achieve similar effects in his 1988 animated film adaptation of the manga by incorporating a blend of manga and cinematic techniques. Some of these are taken from the original AKIRA manga, others from cinematic influences, particularly western ones. The film adapts the manga in a sympathetic way, but also changes a great deal, especially with regard to the presentation of space, sound, perspective and violence. Much of what the manga alludes to, or leaves in the gutters for the reader's imagination to concoct, is translated to the screen to quite different effect. This article will also consider the translation of the manga into English, and how the changes in, for example, sound effects, as well as the addition of colour alter the precision engineering of O-tomo's pages. These two forms of translation (from one language to another, and from page to screen) will be considered alongside one another to reveal the complexity of O-tomo's masterpiece in both media, and the difficulties of such adaptations and translations.